Recurrent pancreatitis due to parathyroid adenoma in pregnancy - Boorugu, Hari Kishan; Surapaneni, Tarakeswari; Vadlamani, Hemamalini; Patel, Devang; Yalamanchili, Shanthi (Indian Journal of Case Reports, 2020)
Hyperparathyroidism complicating pancreatitis is relatively rare in pregnancy, but it is associated with significant maternal and fetal morbidity. This case report describes a pregnant lady with recurrent pancreatitis. Etiologic workup for recurrent pancreatitis revealed hypercalcemia secondary to hyperparathyroidism. The management of hyperparathyroidism includes treatment of hypercalcemia and definitive management of hyperparathyroidism which is the surgical excision of the abnormal gland. However, the timing of the surgery in a pregnant woman needs to be individualized. A multidisciplinary team approach is mandatory for better outcomes.